Flexible thiourea linked covalent organic frameworks. Issue 43 (26th October 2021) - Ma, Baiwei; Li, Chunzhi; Zhang, Lin; Zhai, Lipeng; Hu, Fujia; Xu, Yimeng; Qiao, Huijie; Wang, Zhuo; Ai, Wenying; Mi, Liwei
Abstract : Exploring covalent organic frameworks with new linkages is regarded as an efficient method to modulate the corresponding properties, and a new linkage is essential to the progress of this field. Abstract : Exploring covalent organic frameworks with new linkages is regarded as an efficient method to modulate the corresponding properties, and a new linkage is essential to the progress of this field. Herein, condensation of 1, 3, 5-triformylphloroglucinol with 1, 1′-(1, 4-phenylene)bis(thiourea), 1, 1′-(2, 5-dimethyl-1, 4-phenylene)bis(thiourea) or 1, 1′-(3, 3′-dimethyl-[1, 1′-biphenyl]-4, 4′-diyl)bis(thiourea) were applied to construct COFs with thiourea linkages for the first time.